EXCELLENT SCHOOL, STATUS AND ITS EXISTENCE - Syarwan Ahmad (Universitas Islam Negeri Banda Aceh, 2014)
The excellent school and effective school share their characteristics. Their main characteristic is that higher student academic achievement and there is no disparity or gap across the scores gained. The status of the excellent school is a dynamic process. It should not be decided by educational authorities. The existence of the excellent school has become heated discussions lately. The status of the government supported excellent schools including the RSBI (International Standard School Pilot Project) has recently been revoked. However, the existence of the school should be maintained. Further research on the excellent school is badly needed.